Palliative care for disease with uncertain disease trajectory: an ethical case learning - Taib, Fahisham; Fatima, Eisha; Abdullahi Faruk, Jamil; Syed Abd Hamid, Syed Abdul Khaliq (Penerbit Universiti Sains Malaysia and Malaysian Association of Education in Medicine and Health Sciences, 2019)
Disease trajectory in children can be difficult to determine. This is primarily, despite the life limiting condition, healthcare professionals are unable to pin the exact time when these children’s lives will end. We illustrate an unusual case of dicephalic parapagus, an inseparable conjoined twin which was complicated by anomalies, psychosocial and safeguarding issues. Such case posed a challenge even to paediatric palliative care team as the trajectory of the disease, in this case, is rather difficult to predict. Anticipatory symptoms management perhaps is the best way forward, despite having to face many ethical challenges and medical enigma.